1995
DOI: 10.1063/1.1146032
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of thermoelectric power using metal opposed anvil cells up to 100 kbar

Abstract: In this paper we describe the design of a simple Bridgman opposed anvil cell to measure the thermoelectric power of solids as a function of pressure up to 100 kbar. The anvils are made of EN-24 alloy steel hardened to RC55.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
2
3
1
Order By: Relevance
“…The polycrystalline nature of our samples alleviates the significance of orientation; however, if any preferred orientation is introduced when pressurizing the sample, it may contribute to the variations. Although there is a significant difference in the values between our measurements and those of Ferdin et al (1995), the values shown in Figs. 7(a) and 7(b) are from separate experimental runs and thus provide evidence for consistency for our apparatus when measuring the Seebeck coefficient under the given experimental conditions.…”
Section: Isobaric Seebeck Coefficient Of Bicontrasting
confidence: 72%
See 2 more Smart Citations
“…The polycrystalline nature of our samples alleviates the significance of orientation; however, if any preferred orientation is introduced when pressurizing the sample, it may contribute to the variations. Although there is a significant difference in the values between our measurements and those of Ferdin et al (1995), the values shown in Figs. 7(a) and 7(b) are from separate experimental runs and thus provide evidence for consistency for our apparatus when measuring the Seebeck coefficient under the given experimental conditions.…”
Section: Isobaric Seebeck Coefficient Of Bicontrasting
confidence: 72%
“…Measurements performed by Ferdin et al (1995) show a similar trend for the Seebeck coefficient as a function of pressure. Although the trend agrees, there is a difference between the values as measured in our experiment when compared with those reported by Ferdin et al (1995). As discussed for the results of the temperature measurements, the differences between the two measurements may be attributed to different experimental conditions.…”
Section: Isobaric Seebeck Coefficient Of Bisupporting
confidence: 56%
See 1 more Smart Citation
“…The data are in qualitative agreement with earlier data collected by Bridgman anvil high-pressure techniques (the thermopower of bismuth is anisotropic and the sample was not aligned in a particular crystallographic orientation). 33 The phase transitions in bismuth near 2.5 and 7.7 GPa are visible.…”
Section: Discussionmentioning
confidence: 94%
“…At present there are only a few types of high-pressure cells for thermopower measurement, including the large-volume compressible capsules with a liquid media [31,32], DACs with a cross temperature difference [33][34][35][36], and some others [37].…”
Section: Methodsmentioning
confidence: 99%